The effect of rising prices of subsidized fuel on the use of private cars - Yosritzal, Yosritzal; Anisa, Zahra; Putri, Elsa Eka (Akademisi dan Saintis Indonesia (ASASI), 2024)
The rising fuel prices on September 3, 2022, are expected to reduce the use of private cars and increase the use of public transport. This expectation has raised optimism among public transport operators and is expected to encourage them to invest more. However, there is no evidence to support the expectation. Therefore, it is essential to study the effect of the fuel price on the use of a particular transport mode, thus motivating this study. This paper aims to investigate the impact of the rising costs of subsidized fuel on private cars. A Likert-scale type of questionnaire was used to collect data. The data was analyzed descriptively, and then a conclusion was made based on the results. The study found that the daily commute of respondents changed after fuel prices increased. Distance, duration, and frequency of travel tend to be reduced and prioritized over primary activities. To reduce travel costs, the respondents who usually use cars are more likely to use motorcycles than public transport. The findings of this study disprove that an increase in fuel prices would increase the use of public transport. Why is public transport less favoured compared to motorcycles? It seems that the quality of service provided by public transport fails to satisfy the consumers' needs.